2017
DOI: 10.2208/kaigan.73.i_1171
|View full text |Cite
|
Sign up to set email alerts
|

Study on Numerical Ocean Model in Coastal Regions of Kashima-Nada and Kujukuri

Abstract: 2 国立研究開発法人水産研究・教育機構 水産工学研究所 (〒314-0408 茨城県神栖市波崎7620-7) 3 正会員 防衛大学校教授 システム工学群建設環境工学科 (〒239-8686 神奈川県横須賀市走水1-10-20) 4 正会員 国立研究開発法人水産研究・教育機構 水産工学研究所 (〒314-0408 茨城県神栖市波崎7620-7) 5 正会員 株式会社アルファ水工コンサルタンツ (〒104-0045 東京都中央区築地3-9-9 ラウンドクロス築地9F) 開放性沿岸域である鹿島灘・九十九里浜沿岸海域において,流動特性・物理環境特性を把握するために, 超音波多層流速計・水温塩分計を用いた係留系観測および多項目水質計を用いた鉛直断面観測の現地観測 結果と,Princeton Ocean Modelをベースとした数値計算結果を比較することにより,数値モデルの再現性 について検討を行った.計算結果は,潮汐による水位変動,低気圧の通過に伴う流速の増大や観測前半の 水温・塩分変動など観測結果を比較的良好に再現していた.また,北寄りの風が強化されることで南向き の流れが卓越し,利根川由来の低塩分水が犬吠埼を回り込むよう… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Makino and Nobuoka (2016) probabilistically estimated storm surge and showed that it was possible to minimize local variations by regional frequency analysis and to predict average storm surge inundation. Endo et al (2017) found that the low salinity waters from Tone River sometimes flow into the coastal zone of Kujukuri due to southward current flow and that warm waters sometimes flow toward Kashima-Nada. More recently, Troselj et al (2018) and Troselj et al (2019) conducted dynamical downscaling of coastal dynamics emphasizing freshwater impact from three major rivers and seasonal variabilities of SST and SSS, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Makino and Nobuoka (2016) probabilistically estimated storm surge and showed that it was possible to minimize local variations by regional frequency analysis and to predict average storm surge inundation. Endo et al (2017) found that the low salinity waters from Tone River sometimes flow into the coastal zone of Kujukuri due to southward current flow and that warm waters sometimes flow toward Kashima-Nada. More recently, Troselj et al (2018) and Troselj et al (2019) conducted dynamical downscaling of coastal dynamics emphasizing freshwater impact from three major rivers and seasonal variabilities of SST and SSS, respectively.…”
Section: Introductionmentioning
confidence: 99%